Gestão democrática da saúde pública: reflexão sobre os benefícios que o SUS disponibiliza aos usuários no município de Mariluz - Rosa, Iracy Martins de Almeida (2011)
This work had as its theme the democratic management of public health, presents atheoretical approach reflective of the Brazilian public health, focusing on the Municipal Health Secretariat of the city of Mariluz. Discusses the construction ofuniversal rights, the trajectory of health in Brazil, reflects on the relevant legislationand health services currently offered. Based on the literature relevant to the topic,discusses the quality of services provided. The study found problems that afflict theBrazilian daily life and brings the study as a result of reflections on the principles ofdemocratic management in public health and how it is being conducted for the realization of rights historically conquered by man.